Comparison of Soil Respiration and Carbon Dynamics Under Different Shorea Peltata at Tenggaroh Forest Reserve, Johor, Malaysia - Abdalmoula, Musalam Mohammed (2010)
Soil respiration is an indicator of biological activity of soil life. This activity is important to the soil system as healthy lungs are to use. A field experiment was conducted in Tenggaroh Forest Reserve, Johor to compare soil respiration and carbon dynamic of natural forest reserve under different density of Shorea peltata. The objectives of this study were: to investigate soil respiration under different site characteristics of Shorea peltata, to understand the factors that influence the occurrence of soil respiration in relation to vegetation association and to determine the relationship between soil respiration and soil physical properties under different density of Shorea peltata. Twenty observational plots 50 x 50 m with different density of Shorea peltata namely, rare (E1), low (E2), moderate (E3) and high (E4) were established in compartments 135 and 136. Each plot was divided into 25 subplots, and five subplots were selected at random for soil sampling. Soil samples consisting of topsoil 0 – 10 cm and 10 – 30 cm were taken to determine the physical and chemical properties. Environmental factors such as light intensity, wind speed, relative humidity, and air temperature were recorded in the study site using environmental meter. For the lab analysis, the soil physical and chemical properties such as soil moisture content, soil texture, bulk density, particle density, porosity, pH, soil organic matter, total carbon, total nitrogen, and available of sulphur were analyzed. Soil respiration characteristics were also recorded at all sites of the study area with used LCpro+ instrument at 0 to 6 cm depth. Results show that there are three layers of Shorea peltata species namely (1) dominant, (2) understorey and (3) shrubs. It was also observed that in certain localities, the abundance of this species were not very high. The results of soil respiration and carbon dynamic under different sites showed significant differences at P<0.05 among groups. Analysis for the relationship between soil respiration and environmental variables (correlation) showed that the light intensity, air temperature, soil moisture content, pH, texture, C, N, and sulphur were the important factors in the distribution of vegetation in Tenggaroh Forest Reserve. This implies that the site preferences and density of Shorea peltata were also influenced by these factors. The results of soil analysis showed that the soil physical properties were significantly different at (P<0.05) among groups. Certain physical properties such as moisture content and soil texture were significantly influenced the distribution of Shorea peltata. The environmental factors also showed a strong relationship with the distribution of Shorea peltata. Soil chemical properties were not significantly different among groups at (P<0.05). The degrees of acidity were extremely high in the study area. The overall status of the entire soil samples were relatively lower which showed that plants in the present study seem to be adapted to a relatively poor supply of N, S and acidic soil pH